Investigation of flight technical error for UAV separation requirement based on flight trajectory data - Pang, Bizhao (2022)
With the fast development of unmanned aircraft vehicle (UAV) operations in urban environments, the low-altitude air traffic is projected to be crowded. That would bring about problems such as how to determine the safe separation between two UAV operations. This paper proposes an evaluation framework for the determination of flight technical error (FTE) by investigating flight trajectory deviations, which is to support the establishment of separation requirement for UAV operations. Flight experiments are conducted by using a commonly used drone to collect flight trajectory data. Statistical analysis methods are used to investigate the trajectory deviations on lateral, longitudinal, and vertical axes. The normality tests are first conducted for the trajectory deviation data. The analysis of variance (ANOVA) is then performed to test the homogeneity of sample variances, while the regression analysis is conducted to investigate potential trends of the trajectory deviations with the change of flight heights. Statistical testing results show that the mean trajectory deviation in different flight times has no significant difference, whereas the mean trajectory deviation increases with the increase of flight height. The results also show that the linear increasing trend is more evident for deviations on the lateral track, while the quadratic increasing trend of trajectory deviation dominates on the longitudinal track. The deviations on vertical track is not significant compared with the ones on lateral and longitudinal tracks. This study investigates the flight technical error by analyzing the flight trajectory deviations, which will support the determination of separation requirement for safe UAV operations in low-altitude urban airspace.